The Power of Affiliation: Dynastic Blood, Artificial Kinship and Legitimation Strategies. The Case of the Della Rovere Dukes of Urbino*. (2nd January 2021) - Becker, Sebastian
ABSTRACT: After the Montefeltro dynasty's demise in 1508, the Della Rovere family assumed power in the geo-strategically and culturally important Duchy of Urbino. The first dynasty of papal nephews able to preserve successfully the territory conferred by their family popes beyond the pontifical term, they became a model for upcoming papal families. As 'new princes', they needed to legitimise their new rank and membership of princely society, and also to establish for their subjects the lawful circumstances of their succession. In 1504, Pope Julius II della Rovere had urged the childless Guidobaldo da Montefeltro to adopt their joint nephew, Francesco Maria della Rovere, son of Guidobaldo's sister, Giovanna da Montefeltro, and the Pope's brother, Giovanni della Rovere. This article reviews the basis of this adoption in Roman and Canon law, and shows how it affected contemporaries' belief in the legitimacy of the Della Rovere's succession and was used prominently in the dynasty's self-fashioning.